Композити як одне з основних джерел розвитку і збагачення словникового складу англійської мови (на матеріалах британського національного корпусу текстів (BNC) - Дубравська, Д.М. (Лінгвістика ХХІ століття: нові дослідження і перспективи, 2011)
У статті розглянуто основні характеристики композитів як продуктивного способу словотворення, проаналізовано різні підходи до класифікації композита як феномену, подано результати лінгвістичного дослідження графічного зображення композитів та частотності їх використання в сучасної англійської мові (на матеріалах Британського національного корпусу текстів (BNC). Виділено основні характеристик ендоцентричних та екзоцентричних композитів. В статье рассмотрены основные характеристики композита как продуктивного способа словообразования, проанализированы разные подходы к классификации композита как феномена, представлены результаты лингвистического исследования графического изображения композитов и частотности их использования в современном английском языке (на материалах Британского национального корпуса текстов (BNC). Выделены основные характеристики так называемых эндоцентрических и экзоцентрических композитов. The article examines the phenomenon of composite (compound) as the productive mean of word-formation. The different approaches to the classification of the phenomenon of composits in English are analyzed. The results of the linguistic research of the spelling of composites in Modern English are given (based on the British National Corpus (BNC). The spelling of English compounds depends on the complexity of their constituents. The relevant generalization seems to be that spellers tend to insert a space in compounds if any of its constituents is morphologically complex. In respect to the first constituent this tendency is particularly strong, so that solid compounds in English are overwhelmingly written with a monomorphemic first constituent. The exceptions to this generalization are not numerous and almost all can be accounted for in a principled way. The compound types which are easier to process are more frequent, and are also more often spelled solid. According to the proposed analysis of English compounds, solid compounds seem to differ from open compounds in four important features: spelling, morphological structure, and productivity.